MORLET’S WAVELET ANALYSIS ON EL NIÑO SOUTHERN OSCILLATION (ENSO) AND THE INDIAN OCEAN DIPOLE (IOD) FOR 84 YEARS: 1940-2023 - Suhadi, Suhadi; Putri, Jamiatul Khairunnisa; Iskandar, Iskhaq; Supari, Supari; Irfan, Muhammad; Ariska, Melly; Akhsan, Hamdi (Universitas Mataram, 2024)
As is known, the impact caused by El Niño Southern Oscillation (ENSO) and the Indian Ocean Dipole (IOD) can reach extreme levels, especially rainfall in Indonesia. So, updating information on events and cycles of these phenomena is essential. Using Sea Surface Temperature (SST) data spanning the previous 84 years (1940–2023) from ERA5, we examined Sea Surface Temperature Anomalies (SSTA), which serve as a predictive tool for ENSO and IOD events. Apart from that, in this research, SSTA variance analysis was also carried out using Wavelet. The analysis results show several Positive IOD-Like events (1943, 1944, 1977, 1996) and Negative IOD-Like (1985, 1992, 2016). Apart from that, the results of this research also show that El Niño in 2002/03 coincided with Negative IOD in 2002. The results of Wavelet analysis show that the SSTA DMI variance experienced increased activity in the periods 1940-1968, 1969-1991, and 1992-2023. The Wavelet analysis also shows that ENSO activity increased in 1970-2000 and decreased again in 2000-2023.